2020
DOI: 10.3390/ijerph17196990
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Oral Glucose Tolerance Test Abnormalities and Adverse Pregnancy Outcomes in Gestational Diabetes: A Cross-Sectional Study

Abstract: Gestational diabetes mellitus (GDM) is associated with maternal and neonatal complications. We aimed to evaluate the relationship between the abnormalities of the oral glucose tolerance test (OGTT) and adverse pregnancy outcomes. This was a retrospective study of GDM patients over a five-year period in a Malaysian tertiary center. The diagnosis of GDM was based on the National Institute for Health and Care Excellence (NICE) guideline. The data on patients’ demographics, OGTT results, GDM treatment, and pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, others reported that although optimizing blood glucose treatment can reduce the risk of PE, it is not an independent influencing factor, but the OGTT fasting blood glucose level is independent and significantly correlated with the occurrence of PE (23). Accordingly, two other studies also support the finding that OGTT blood glucose levels are an independent risk factor for the development of PE (93,94). A Chinese retrospective cohort study reported that the blood glucose level at OGTT and after treatment of GDM did not independently predict the occurrence of PE, while the fasting blood glucose level at OGTT is an important risk factor for such (54).…”
Section: Blood Glucosementioning
confidence: 93%
“…However, others reported that although optimizing blood glucose treatment can reduce the risk of PE, it is not an independent influencing factor, but the OGTT fasting blood glucose level is independent and significantly correlated with the occurrence of PE (23). Accordingly, two other studies also support the finding that OGTT blood glucose levels are an independent risk factor for the development of PE (93,94). A Chinese retrospective cohort study reported that the blood glucose level at OGTT and after treatment of GDM did not independently predict the occurrence of PE, while the fasting blood glucose level at OGTT is an important risk factor for such (54).…”
Section: Blood Glucosementioning
confidence: 93%
“…Taking into consideration about 10% of incomplete or missing data in the home-based records, the sample size needed is 292 (263/0.90) cases and 584 (526/0.90) control at the ratio of 1:2. Knowing the average number of pregnancies at each of the six participating clinics (200–300 cases and 1500–3000 controls per year) and the required 1:10 ratio of independent variables to numbers of dependent variables to run a multiple logistic regression with 14 independent variables on GDM with any maternal or neonatal complication rate of 40%, 61 the study is deemed to be feasible. Therefore, we will continue to collect the home-based records from the postpartum women until at least 876 records have been collected.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Defects in fasting and postprandial glucose metabolism are precipitated by different mechanisms 38. In a recent review, it was concluded that hepatic insulin resistance is a dominant feature in isolated IFG and peripheral insulin resistance is a characteristic of those with isolated IGT 39. Several interventional studies have furnished epidemiological evidence for these.…”
Section: Discussionmentioning
confidence: 99%
“…38 In a recent review, it was concluded that hepatic insulin resistance is a dominant feature in isolated IFG and peripheral insulin resistance is a characteristic of those with isolated IGT. 39 Several interventional studies have furnished epidemiological evidence for these. For example, a fasting blood glucose abnormality was determined to be a positive predictor for insulin therapy, [40][41][42] whereas a 2-hour glucose derangement was significantly associated with diet therapy and reduced risk of insulin usage.…”
Section: Open Accessmentioning
confidence: 99%